Exposure to chronic mild stress prevents kappa opioid-mediated reinstatement of cocaine and nicotine place preference - Al-Hasani, Ream; McCall, Jordan G.; Bruchas, Michael R. (Frontiers in Pharmacology, 2013)
Stress increases the risk of drug abuse, causes relapse to drug seeking, and potentiates the rewarding properties of both nicotine and cocaine. Understanding the mechanisms by which stress regulates the rewarding properties of drugs of abuse provides valuable insight into potential treatments for drug abuse. Prior reports have demonstrated that stress causes dynorphin release, activating kappa-opioid receptors (KOR) in monoamine circuits resulting in both potentiation and reinstatement of cocaine and nicotine conditioned place preference. Here we report that kappa-opioid dependent reinstatement of cocaine and nicotine place preference is reduced when the mice are exposed to a randomized chronic mild stress regime prior to training in a conditioned place preference-reinstatement paradigm. The chronic mild stress schedule involves seven different stressors (removal of nesting for 24hr, 5min forced swim stress at 15°C, 8hr food and water deprivation, damp bedding overnight, white noise, cage tilt and disrupted home cage lighting) rotated over a three-week period. This response is KOR-selective, because chronic mild stress does not protect against cocaine or nicotine drug-primed reinstatement. This protection from reinstatement is also observed following sub-chronic social defeat stress, where each mouse is placed in an aggressor mouse home cage for a period of 20 min over five days. In contrast, a single acute stressor resulted in a potentiation of KOR-induced reinstatement, similarly to previously reported. Prior studies have shown that stress alters sensitivity to opioids and prior stress can influence the pharmacodynamics of the opioid receptor system. Together, these findings suggest that exposure to different forms of stress may cause a dysregulation of kappa opioid circuitry and that changes resulting from mild stress can have protective and adaptive effects against drug relapse.